An elderly man with gastric cancer, Saint’s triad and Heyde’s syndrome - Santos, Vitorino M. (2018)
This case study describes a 71-year-old man with signet-ring cell gastric adenocarcinoma and malignant sigmoidal polyp; and typical features of Saint’s triad and Heyde syndrome. He had digestive bleeding, two types of hernia, diverticulosis, arterial hypertension, malignant polyp, and antecedent of smoking, lung tuberculosis, and surgical correction of aortic valve stenosis. There is a hypothetical inverse relationship between herniosis and development of malignancy; however, the patient herein described presented gastric and sigmoidal cancers. Gastrointestinal malignancies are sometimes associated with paraneoplastic entities, isolated or manifested as syndromes, but neither Saint’s triad or Heyde syndrome have been included. This patient persisted clinically stable during the preoperative period, but suddenly died; Trousseau’s syndrome would be the most probable mechanism of sudden death in this setting. Case reports can stimulate further studies to get additional knowledge about unusual entities.